First-Principles Study of Electronic and Nonlinear Optical Properties of Halides and Rubidium Halides Substituted Anthracene Diimide - S. Augustine, Njapba; Barsisa , Buba (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study reports the density functional theory calculations of UV-Visible, HOMO-LUMO energy band gap as measure of reactivity, nonlinear optical properties and natural bond orbital properties of novel Anthracene diimide derivatives. The UV-Visible absorption peak resulting from electronic transitions HOMO-LUMO observed to be the highest among others for ADI-Rb2I2 occurs at 77.94 nm is also in good agreement with the experimental value. The HOMO-LUMO energy band gap has been found to be reasonably small ≈ 0.54 eV. The total frequency-dependent polarizability for RHF method is remarkably positive and far greater than the values obtained using B3LYP functional. This variation in the total frequency-dependent polarizability is due to the sensitivity of the nonlinear optical property to the functional. Our calculation of total static first order hyperpolarizability with RHF method and B3LYP functional are approximately 1.9, 28, 73, 161, 2309, 0.08, 26, 35, 44, 53, 114, and 454 many times greater than the standard compound Urea. These results indicate that Anthracene diimide substituted halides and rubidium halides are suitable for nonlinear optical applications. Natural bond orbital analysis reveals that donor LP (3) O22→π*(N24-C28) acceptor interactions corresponds to the highest second order perturbation energy E2 = 111.11 kcal/mol associated with electron delocalization.